Nicotinamide abrogates acute lung injury caused by ischaemia/reperfusion - Su, C-F; Liu, D D; Kao, S J; Chen, H I (The European respiratory journal, 2007)
Poly (ADP-ribose) synthase or polymerase (PARS and PARP, respectively) is a cytotoxic enzyme which causes cellular damage. Nicotinamide, a compound of vitamin B complex, has been reported to exert an inhibitory effect on PARS or PARP. The present study tests the effects of nicotinamide on acute lung injury and associated alterations following ischaemia/reperfusion (I/R) of the isolated perfused rat's lung. I/R increased the lung weight (LW) to body weight ratio, LW gain, protein and dye tracer leakage, pulmonary arterial pressure and capillary permeability. The insult also increased nitrate/nitrite, methyl guanidine, tumour necrosis factor-alpha and interleukin-1beta in lung perfusate, while it decreased adenosine triphosphate content with an increase in PARP activity in lung tissue. Most of the I/R-induced changes were abrogated by post-treatment (30 min after I/R) with nicotinamide (100 mg.kg(-1) body weight). However, the increase in pulmonary arterial pressure was enhanced by nicotinamide post-treatment. Following I/R, the inducible nitric oxide synthase (iNOS) mRNA expression was enhanced. Nicotinamide reduced the iNOS expression. The results suggest that nicotinamide exerted a protective effect on the acute lung injury caused by ischaemia/reperfusion. The mechanisms may be mediated through the inhibition on the poly (adenosine diphosphate-ribose) polymerase activity, inducible nitric oxide synthase expression and the subsequent suppression of nitric oxide, free radicals and pro-inflammatory cytokines with restoration of adenosine triphosphate.